2016
DOI: 10.1080/17425247.2016.1211638
|View full text |Cite
|
Sign up to set email alerts
|

Crush resistance and insufflation potential of poly(ethylene oxide)-based abuse deterrent formulations

Abstract: Testing methods for crush resistance may not be applicable to all products nor allow control over all process factors. Notwithstanding, the use of high-powered electrical devices may be an effective discriminatory tool for testing heat treated PEO-based ADFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Application of heat, such as during the printing process, also changes the physical state of PEO, resulting in high mechanical strength, thereby making its use favourable for abuse-deterrence. Thus, it can be concluded that printlets containing PEO are more resistant to abuse through the nasal route when compared to heat-treated PEO tablets previously reported by Muppalaneni et al (Muppalaneni et al, 2016). In vitro dissolution studies show that despite the addition of the PEO, the formulations still retained their alcohol-resistant properties, wherein ƒ2 similarity values of and 84…”
Section: Resultsmentioning
confidence: 49%
“…Application of heat, such as during the printing process, also changes the physical state of PEO, resulting in high mechanical strength, thereby making its use favourable for abuse-deterrence. Thus, it can be concluded that printlets containing PEO are more resistant to abuse through the nasal route when compared to heat-treated PEO tablets previously reported by Muppalaneni et al (Muppalaneni et al, 2016). In vitro dissolution studies show that despite the addition of the PEO, the formulations still retained their alcohol-resistant properties, wherein ƒ2 similarity values of and 84…”
Section: Resultsmentioning
confidence: 49%
“…A separate study also suggested that method of comminution used had the most prominent effect on tablet fragment size when powerful electric instruments such as high shear grinders are used. 23 Given this, we may conclude that grinding tablet compacts and further sieve analysis may not be the best determinant for such tamper resistant testing. The use of dynamic image analysis to assess the particle size of PEO based tablets crushed using a coffee grinder did show that the biggest factor affecting particle size was the curing temperature; higher curing temperatures and times resulted in more coarse particles.…”
Section: Resultsmentioning
confidence: 99%
“…We considered the percent of fragments greater than 850 µm as an indication of crush resistance by commonly available household comminution practices. 23 We therefore used “% of fragments >850 µm” throughout the paper as an indicator of tablet compact mechanical strength. The higher the percentage of larger particles (>850 µm), the greater is the resistance to crushing, chewing, and grinding.…”
Section: Methodsmentioning
confidence: 99%
“…These are common household items used for tampering with prescription opioid medications. For PSR, the intact pellets were hit by a hammer with ten repeated strokes (Muppalaneni et al, 2016). Approximately 5 g of each formulation was weighed, and placed in a motor or coffee blender, and ground for 3 min using a pestle and 1-3 min in the coffee blender.…”
Section: Physical Manipulation and Particle Size Reduction-mentioning
confidence: 99%